Maame eaudiobook - George, Jessica (Macmillan Audio, 2023)
A Today Show #ReadWithJenna Book Club Pick One of BookPage 's Best Audiobooks of 2023 "The patchwork elements cooperate with one another both on the page and in the audiobook, thanks to Heather Agyepong's elegant narration." — New York Times " Maame is a deeply funny yet emotional novel that comes alive with narration. A great pick for the twenty-something trying to make their way in the world, this audiobook will have you laughing on your commute to work." — USA Today "Sardonic, authentic, and a little bit sad, it moves along at a brisk pace. Compulsively listenable." — Vulture Maame (ma-meh) has many meanings in Twi but in my case, it means woman. It's fair to say that Maddie's life in London is far from rewarding. With a mother who spends most of her time in Ghana (yet still somehow manages to be overbearing), Maddie is the primary caretaker for her father, who suffers from advanced stage Parkinson's. At work, her boss is a nightmare and Maddie is tired of always being the only Black person in every meeting. When her mum returns from her latest trip to Ghana, Maddie leaps at the chance to get out of the family home and finally start living. A self-acknowledged late bloomer, she's ready to experience some important "firsts": She finds a flat share, says yes to after-work drinks, pushes for more recognition in her career, and throws herself into the bewildering world of internet dating. But it's not long before tragedy strikes, forcing Maddie to face the true nature of her unconventional family, and the perils — and rewards—of putting her life on the line. Smart, funny, and deeply affecting, Jessica George's Maame deals with the themes of our time with humor and poignancy: from familial duty and racism, to female pleasure, the complexity of love, and the life-saving power of friendship. Most important, it explores what it feels like to be torn between two homes and cultures―and it celebrates finally being able to find where you belong. "Meeting Maame feels like falling in love for the first time: warm, awkward, joyous, a little bit heartbreaking and, most of all, unforgettable." — Xochitl Gonzalez, New York Times bestselling author of Olga Dies Dreaming A Macmillan Audio production from St. Martin's Press.